Steric effects of bulky tethered arylpiperazines on the reactivity of Co-Schiff base oxidation catalysts—a synthetic and computational study. Issue 23 (7th June 2019) - Key, Rebecca E.; Elder, Thomas; Bozell, Joseph J.
Abstract: New C2-symmetric and C2-asymmetric Co-Schiff base catalysts tethered to arylpiperazine units were synthesized and used to oxidize phenolic lignin models to para -benzoquinones. Synthetic approaches to these catalysts were optimized to include fewer steps and broaden the types of catalyst structures available. In contrast to conventional Co-Schiff base catalysts, these systems induce phenolic oxidation in the absence of an external axial base, simplifying the process. Asymmetric catalysts bearing a phenylethylene or diphenylmethyl piperazine substituent display the highest catalytic activity observed to date for the conversion of S-models to 2, 6-dimethoxybenzoquinone (DMBQ). Computational analysis shows that more reactive catalysts populate conformations that favor oxidation in preference to non-productive decomposition routes. This balance between catalyst reactivity and catalyst deactivation is optimized by inclusion of sufficient steric bulk around the periphery of the Schiff base ligand, reducing catalyst deactivation and allowing oxidations to proceed in the absence of an added axial ligand. Graphical abstract: Image 1